Intelligent gather optimization for radial interpolation seismic gathers using the multi-objective mayfly algorithm - Zhang, Wei; Yan, Songhong; Liao, Zheyuan; Sun, Weiyu; Xu, Pengyu; Sun, Shoubang (Journal of geophysics and engineering, 2025)
Abstract As a special type of azimuth-based pre-stack seismic gather, the optimization of radial interpolation offset gathers differs from conventional pre-stack offset gather process, with the key focus being the determination of stack coefficients across multiple azimuths. Based on this, this study systematically integrates conventional gather optimization techniques such as filtering, inverse Q filtering, generalized Wiener–Levinson deconvolution, and gather flattening. Multiple sub-objective functions were established for gathers at different azimuths and angles, and both single-objective and multi-objective mayfly algorithm were applied for optimization, introducing the concept of the “optimal stack coefficient.” The results demonstrate that the proposed method significantly improves seismic data resolution and enhances the correlation between well-side seismic gathers and synthetic records, while maintaining consistent amplitude versus offset characteristics before and after optimization. Ultimately, this research provides a theoretical foundation and technical support for the processing of radial-interpolated pre-stack offset gathers.